Bovine colostrum supplementation and upper respiratory symptoms during exercise training: a systematic review and meta-analysis of randomised controlled trials. Issue 1 (December 2016) - Jones, Arwel; March, Daniel; Curtis, Ffion; Bridle, Christopher
Abstract Background Bovine colostrum is proposed as a nutritional countermeasure to the risk of upper respiratory symptoms (URS) during exercise training. The aim of this systematic review and meta-analysis was to estimate the size of the effect of bovine colostrum supplementation on URS. Methods Databases (CDSR, CENTRAL, Cinahl, ClinicalTrials.gov, Current Controlled Trials, DARE, EMBASE, Medline, PROSPERO and Web of Science) of published, unpublished and ongoing studies were searched for randomised controlled trials of healthy adults (≥18 years), evaluating the effect of oral bovine colostrum supplementation compared to a concurrent control group on URS. Results Five trials (152 participants) met the inclusion criteria, all of which involved individuals involved in regular exercise training. Over an 8–12 week follow-up period, bovine colostrum supplementation when compared to placebo significantly reduced the incidence rate of URS days (rate ratio 0.56, 95 % confidence intervals 0.43 to 0.72, P value < 0.001) and URS episodes (0.62, 0.40 to 0.99, P value = 0.04) by 44 and 38 % respectively. There were limited data and considerable variation in results of included studies for duration of URS episodes hence a meta-analysis of this outcome was deemed inappropriate. The risk of bias assessment in this review was hindered by poor reporting practices of included studies. Due to incomplete reporting of study methods, four of the five studies were judged to have a moderate or high risk of overall bias. Our findings must be interpreted in relation to quantity and quality of the available evidence. Conclusions The present systematic review and meta-analysis provides evidence that bovine colostrum supplementation may be effective in preventing the incidence of URS days and episodes in adults engaged in exercise training. The fact that the majority of included studies did not report significant effects on URS outcomes mitigates concerns about publication bias. The point estimates of the random-effects meta-analyses are greater than the smallest clinically important difference, but the low precision of the individual study estimates means the evidence presented in this review needs to be followed up with an appropriately designed and adequately powered, randomised control trial. Trial registration Protocol was registered (CRD42015014925 ) on the International Prospective Register of Systematic Reviews (http://www.crd.york.ac.uk/PROSPERO/ ).